(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: The study aimed to compare the sensitivity and specificity and explore the convenience, acceptance, and cost of patients for Kato-Katz, Ether-formalin, and direct stool tests in diagnosing gastrointestinal helminths. Research method: The quantitative study was conducted on 190 stool samples, including positive controls and samples from suspected patients, using Kato-Katz, Ether-formalin, and direct techniques. At the same time, qualitative research directly interviewed patients coming for parasite examination and testing staff and parasite laboratory managers. Results: As a result, the sensitivity of the three testing techniques is 90.00%, 80.00%, and 70.00%, respectively, and the specificity is 100%. Implementing the Direct Examination technique (100%) in laboratories, but Kato-katz and Ether-formalin techniques are less. The explanation for this problem is that the number of patients per day is too small, it takes time and the procedure is complicated. In comparison, these tests are convenient and reasonably priced for all service providers and recipients of testing services. Conclusion: The clinical use of stool testing techniques depends mainly on the attitude and acceptance of the user.